2010
DOI: 10.1186/1755-8794-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood gene expression patterns discriminate among chronic inflammatory diseases and healthy controls and identify novel targets

Abstract: BackgroundChronic inflammatory diseases including inflammatory bowel disease (IBD; Crohn's disease and ulcerative colitis), psoriasis and rheumatoid arthritis (RA) afflict millions of people worldwide, but their pathogenesis is still not well understood.It is also not well known if distinct changes in gene expression characterize these diseases and if these patterns can discriminate between diseased and control patients and/or stratify the disease. The main focus of our work was the identification of novel mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 50 publications
2
88
0
2
Order By: Relevance
“…[13][14][15][16][17][18] In this study, we identified miR-31, miR-146a, miR-206, and miR-424 as novel miRNA biomarkers that are commonly and specifically expressed in the freshfrozen tissue of colonic mucosa from inflammatory bowel disease patients compared with colonic mucosa control patients. The dysregulated expression of four miRNAs in both ulcerative colitis and Crohn disease suggests that these miRNAs might be involved in the regulation of the common pathophysiological pathway leading to inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] In this study, we identified miR-31, miR-146a, miR-206, and miR-424 as novel miRNA biomarkers that are commonly and specifically expressed in the freshfrozen tissue of colonic mucosa from inflammatory bowel disease patients compared with colonic mucosa control patients. The dysregulated expression of four miRNAs in both ulcerative colitis and Crohn disease suggests that these miRNAs might be involved in the regulation of the common pathophysiological pathway leading to inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of genomic markers, such as mutations in epidermal growth regulator factor (EGFR) or KRAS, may be decisive for the successful treatment of solid and non-solid malignancies, and such information is being increasingly recognized and implemented by regulatory authorities. There is also increasing evidence for the application of personalized medicine in immunological and/or inflammatory diseases [21]. Personalized medicine is actually becoming accepted in oncology much more quickly due both to the diversity and potentially lethal character of the disease and to the narrow therapeutic index and low benefit-risk ratio of the drugs used.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that AQP9 may contribute to neuroinflammation as well, although not investigated. However, AQP9 expression is found in leukocytes (264), and has been found to be upregulated in peripheral blood derived mononuclear cells from patients with inflammatory diseases (461)(462)(463). Nevertheless, both AQP4 and AQP1 are orthodox aquaporins only permeable to water, whereas AQP9 shows a broad permeability specter, suggesting that AQP9 may serve other roles as well.…”
Section: Brain Aquaporins In Pdmentioning
confidence: 99%